RANCANG BANGUN ALAT PENGERING KOPRA PUTIH - Ahmad Saifullah; Andrie Andrie; Rizal Syarifuddin (Program Studi Teknik Industri Fakultas Teknik Universitas Islam Makassar, 2026)
As a tropical country, Indonesia has many natural resources that can be utilized for agricultural purposes. This research aims to design an LPG gas-based white copra dryer and compare the results with traditional sunlight drying methods. The research used a qualitative descriptive method, including literature study, ergonomic analysis, prototype design, and tool testing. The results showed that this white copra dryer uses LPG-based heating that distributes heat evenly throughout the drying chamber. This tool accelerates the drying process from 2-3 days to only 8-10 hours, with moisture content that can be maintained within the ideal range of 8%-9% according to the Indonesian National Standard (SNI). Compared to conventional methods, the dryer produces copra with a more even and bright colour, lower moisture content, better hygiene due to the closed system, better inter-batch consistency, independent of the weather, and increased productivity because drying can be done anytime. Economically, this tool shows an effectiveness rate of more than 85%. The study concluded that this white copra dryer is an appropriate technology solution that can improve the quality and quantity of copra production, reduce weather damage, and contribute to increasing farmers’ income and welfare.